Evaluating the Role and Impact of Tanzanian Trade Unions on Worker’s Welfare from 2016 to 2021 - Loisulie, Paul (iRASD Journal of Management, 2024)
This study appraised the role of the trade unions during the five years of the fifth phase regime in Tanzania in addressing employee’s concerns. The main aim was to assess the views of trade union members on how they view functioning of their unions basing on four dimensions namely structure, value, impact and environment with their indicators. The parameters focused on the common areas that influence functions of trade unions and are vividly assessable. The methodology involved online survey using Google form which was sent to members of trade unions through social media networks. The data collection technique used was unrestricted survey. The findings reveal that majority of respondents are positive on the existence of trade unions in work places but factors like political environment and legal framework are not friendly to smooth running of trade unions. Further, soft skills tactic is found to be more appropriate in solving employee’s grievances compared to hard skills. It is concluded by this study that despite the challenges experienced, unionism is still an important instrument for workers wellbeing in their work places. In addition to that, the spirit of trade unionism never dies, hence the trade unions and employees must learn to coexist in a mutual benefit as guided by industrial relation concept. This study recommends that the concept of industrial relations (labor relations) be enhanced in work places through different approaches like training and capacity building to trade union leaders, members and the management of the institutions (establishment of training programs). Additionally, the study about the future of trade unions in the fast-changing world in all aspects is demanding.